Dose-response relationships in gene expression profiles in a harbor seal B lymphoma cell line exposed to 17α-ethinyl estradiol - Christine Kleinert; Matthieu Blanchet; François Gagné; Michel Fournier (MDPI AG, 2017)
The determination of changes in gene expression profiles with xenobiotic dose will allow identifying biomarkers and modes of toxicant action. The harbor seal (Phoca vitulina) 11B7501 B lymphoma cell line was exposed to 1, 10, 100, 1000, 10,000, or 25,000 μg/L 17α-ethinyl estradiol (EE2, the active compound of the contraceptive pill) for 24 h. Following exposure, RNA was extracted and transformed into cDNA. Transcript expression in exposed vs. control lymphocytes was analyzed via RT-qPCR to identify genes with altered expression. Our analysis indicates that gene expression for all but the reference gene varied with dose, suggesting that different doses induce distinct physiological responses. These findings demonstrate that RT-qPCR could be used to identify immunotoxicity and relative dose in harbor seal leukocytes.